Synthesis and biological activity of pyochelin, a siderophore of Pseudomonas aeruginosa. - Ankenbauer, R G (1988)
Pyochelin, a phenolic siderophore of Pseudomonas aeruginosa, was synthesized in three steps from salicylonitrile, L-cysteine, and L-N-methylcysteine. The synthetic product was determined to be identical to natural pyochelin by 1H nuclear magnetic resonance spectroscopy, fast atom bombardment mass spectrometry, chromatographic analysis, and chemical reactivity with FeCl3 and ammoniacal silver nitrate reagent. Synthetic and natural pyochelin promoted bacterial growth in iron-depleted medium and were also found to mediate iron transport by P. aeruginosa to the same levels. Neopyochelin, a stereoisomeric by-product of the synthesis, showed less biological activity than did pyochelin in iron transport assays.